Hubungan Model Pembelajaran Discovery Learning Dengan Materi Menulis Cerpen Kelas XI SMA Negeri 2 Sungai Kakap - Safitri, Adelia; Arni, Arni; Fitriani, Fitriani (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The aim of this research is to determine the significant relationship between the discovery learning learning model and short story writing material for class XI SMA Negeri 2 Sungai Kakap. The method used in this research is a correlation study method, using a form of relationship study. The population in this study were all class XI students of SMA Negeri 2 Sungai Kakap. The sample used was class XI MIPA 2, totaling 31 students. The data collection method used was the distribution of questionnaires and short story writing tests aimed at measuring the relationship between the discovery learning model and short story writing material. Data analysis uses the product moment correlation formula. The research results obtained an rxy of 0.438 and a 5% significance level table with N = 31 of 0.344. The data shows rxy > rtable which means Ha is accepted and Ho is rejected. So it is concluded that there is a relationship between the discovery learning model and the short story writing material for class XI SMA Negeri 2 Sungai Kakap.